Scene and character: interdisciplinary analysis of musical and sound symbols for higher education (Foro de Educacion, 2017)
The aim of this paper is to analyze interdisciplinary and educationally the descriptive aspects of the characters in literature in the world of music (opera, ballet, musical theater, program music, audiovisual, etc.) through a wide range of resources and creative processes in various skills that include or encompass the sound. Because of that a literature review and multidisciplinary documentary is done from the most relevant texts and principal authors of the dynamic and stable personality models, from the analysis of vocal features in the scene and in the audiovisuals, from the leitmotiv as a symbol and sound representation of the character, from the the conflicts faced by the characters and how they can overcome them and how we could translated into music those transitions. The subject of myths brought to the world of music scene, character stereotypes and sound symbols that may characterize these scenic and literary content is also addressed. Notably, there is a broad consensus on the use of sound resources to characterize the different characters throughout the history of Western music in its various styles and genres. Furthermore, indications for their use are given and suggestions for activities to higher education suggest.